Next-generation thermo-plasmonic technologies and plasmonic nanoparticles in optoelectronics. (May 2015) - De Sio, Luciano; Placido, Tiziana; Comparelli, Roberto; Lucia Curri, M.; Striccoli, Marinella; Tabiryan, Nelson; Bunning, Timothy J.
Abstract: Controlling light interactions with matter on the nanometer scale provides for compelling opportunities for modern technology and stretches our understanding and exploitation of applied physics, electronics, and fabrication science. The smallest size to which light can be confined using standard optical elements such as lenses and mirrors is limited by diffraction. Plasmonic nanostructures have the extraordinary capability to control light beyond the diffraction limit through an unique phenomenon called the localized plasmon resonance. This remarkable capability enables unique prospects for the design, fabrication and characterization of highly integrated photonic signal-processing systems, nanoresolution optical imaging techniques and nanoscale electronic circuits. This paper summarizes the basic principles and the main achievements in the practical utilization of plasmonic effects in nanoparticles. Specifically, the paper aims at highlighting the major contributions of nanoparticles to nanoscale temperature monitoring, modern "drug free" medicine and the application of nanomaterials to a new generation of opto-electronics integrated circuits.